1976
DOI: 10.1007/bf02637389
|View full text |Cite
|
Sign up to set email alerts
|

Rapid densitometric determination of triglyceride groups by argentation thin layer chromatography

Abstract: A method has been developed for the quantitative thin layer chromatographic determination of the triglyceride groups, differing in unsaturation, based on densitometry of the charred bands. Complete separation was achieved by continuous development in an open glass jar. The need for correction coefficients was avoided through addition of bromine to the double bonds prior to charring in the presence of sulphuryl chloride. The accuracy and precision of the method were evaluated on a standard mixture and on sunflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…However, earlier examinations revealed that the procedures chosen to carbonise the separated species ensure accurate results (Chobanov et al 1976;Tarandjiiska et a1 1995). Moreover, since component TAG are determined as area percent relative to the total area of the fractions, reproducibility of charring among different chromatoplates is by no means essential.…”
Section: Accuracy and Precisionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, earlier examinations revealed that the procedures chosen to carbonise the separated species ensure accurate results (Chobanov et al 1976;Tarandjiiska et a1 1995). Moreover, since component TAG are determined as area percent relative to the total area of the fractions, reproducibility of charring among different chromatoplates is by no means essential.…”
Section: Accuracy and Precisionmentioning
confidence: 97%
“…These are usually minor components in highly unsaturated oils and require a larger sample size, On the other hand, the complete resolution of S,, S,M and SM, is easily achieved with mobile phase of light petroleum/acetone (Chobanov et al 1976;Tarandjiiska andNguyen 1988, 1989) (Fig 1A). S3 TAG were not detected in these oils, however, even by high overloading (up to 200 pg per plate).…”
Section: Ag-tlc Separationmentioning
confidence: 98%
See 1 more Smart Citation
“…0.2 mm silica gel G layer and impregnated by dipping into a 0.5% methanolic solution of silver nitrate. The sample size and the mobile phase composition varied depending on the TAG profile of the particular analyzed oil -corn, cotton, and sunflower [20,24] olive, [18] and soybean. [21] Sunflower samples with high oleic acid content were analyzed under chromatographic conditions used 1016 I.…”
Section: Silver Ion-tlc Analysis Of Triacylglycerolsmentioning
confidence: 99%
“…). An aliquot (10 kL) of the derivatized fatty acids was applied by micropipette to a 4 x 19 cm home-made glass TLC plate coated with an 0.2 mm thick silica gel G layer and impregnated (by dipping) in 1 .O% methanolic silver nitrate (Chobanov et al 1976(Chobanov et al , 1992. The plate was developed twice in a nonsaturated closed cylindrical tank (22 x 4.5 cm i.d.)…”
Section: Silver Ion Thin Layer Chromatography (Ag-tlcmentioning
confidence: 99%